A LEGACY OF LEADERSHIP: WOMEN’S CONTRIBUTIONS TO JOS DEVELOPMENT (1999-2023) - Michael, Adeyemi, Oluwaseun; Nwosu , Samuel Elijah (International Research Journal of Arts and Communication, 2024)
This study examines the contributions of women to the development of Jos, a city in northern Nigeria, despite facing various challenges. Using a qualitative research approach, including indepth interviews, focus group discussions, and document analysis, this study reveals the significant impact of women's participation in trade, agriculture, and small-scale enterprises on the city's economic growth. Additionally, women's roles in promoting education, healthcare, and social welfare programs have improved the lives of countless individuals. Furthermore, their involvement in peacebuilding and conflict resolution efforts has fostered harmony and stability in the city. This study highlights the agency, resilience, and dedication of women in shaping Jos' social, economic, and cultural landscape